Modal Analysis of Hyperboloidal-type Normal Circular-arc Gear - Zhang Xiaoping; Shi Donghe; Chen Houjun (Jixie chuandong)
The hyperboloidal-type normal circular-arc gear is a new circular-arc gear used in crossed axis transmission.In order to study its characteristics of vibration,the FEM model is created based on ANSYS.The natural frequency and modes of vibration of pinion and gear are obtained respectively through the modal analysis and the critical speed of rotation is computed.Further,the natural frequencies of pinion and gear under the condition of different number of teeth,modulus and the transmission ratio are calculated.The influence of main geometric parameters on natural frequencies is analyzed and summarized,which provide basic for the optimal design and dynamics research of hyperboloidal-type normal circular-arc gear.